In vitro cytotoxic and in vivo antitumoral activities of some aminomethyl derivatives of 2,4-dihydro-3H-1,2,4-triazole-3-thiones-Evaluation of their acetylcholinesterase and carbonic anhydrase enzymes inhibition profiles - Timur, Irfan; Kocyigit, Umit M.; Dastan, Taner; Sandal, Suleyman; Ceribasi, Ali Osman; Taslimi, Parham; Ciftci, Mehmet (Wiley, 2019)
The 1,2,4-triazole and its derivatives were reported to exhibit various pharmacological activities such as antimicrobial, analgesic, anti-inflammatory, antitumoural, cytotoxic, and antioxidant properties. In this study, a series of triazole compounds (M1-M10) were evaluated for some biological activities. In vitro qualifications of these compounds on acetylcholinesterase (AChE) and human carbonic anhydrase enzyme activities were performed. Also, their antitumoral activities in human colon cancer (HT29) cell line cultures were examined. In addition, colon cancer experimentation was induced in rats by an in vivo method, and the in vivo anticancer effects of triazole derivatives were investigated. Also, the effects of these derivatives in levels of antioxidant vitamin A, vitamin E, and MDA were studied in rat liver and blood samples. Most of the compounds were found to exhibit significant antioxidant and antitumoral activities. All the compounds had cytotoxic activities on HT29 cell lines with their IC50 values lower than 10 mu M concentrations. The low IC50 values of the compounds are M1 (3.88 mu M), M2 (2.18 mu M), M3 (4.2 mu M), M4 (2.58 mu M), M5 (2.88 mu M), M6 (2.37 mu M), M7 (3.49 mu M), M8 (4.01 mu M), M9 (8.90 mu M), and M10 (3.12 mu M).
Keywords: antitumoural activity; carbonic anhydrase; enzyme inhibition; MDA; triazole